A1_7_Can a skydiver without a parachute be saved? - Gosling, Jennifer; Keen, Gemma; Evans, Laura; Evans, Tamsyn (Physics Special Topics, 2009)
This report investigates the speed of freefall of skydivers to determine whether or not it is possible to save someone who falls from a plane without a parachute.Â  We conclude that it is possible, but that the rescuer must jump from the plane within 26.8 seconds of the person who fell.